Frequency transmitting and receiving device for preventing fake plates and traffic congestion of automobile management system - LUO MUXU (2014)
The invention discloses a frequency transmitting and receiving device for preventing fake plates and traffic congestion of an automobile management system and belongs to the technical field of fake plates and traffic congestion prevention of automobile management and safety driving systems. The automobile management system comprises roadside networked frequency transmitting devices and a monitoring camera, wherein road traffic can be known about through the frequency transmitting devices by means of the monitoring camera and signal plate numbers. The frequency transmitting devices are arranged on different roadsides and have different customized frequency transmitting prompt messages. When discovering traffic congestion or traffic accidents, the frequency transmitting devices are connected with the internet to perform forwarding to prompt road conditions, and a system management center can transmit road traffic emergency to vehicles behind positions where road traffic emergency happens to prompt safe driving.